Spin resolved photoelectron spectroscopy of [Mn6IIICrIII]3 +single-molecule magnets and of manganese compounds as reference layers - Helmstedt, Andreas; Müller, Norbert; Gryzia, Aaron; Dohmeier, Niklas; Brechling, Armin; Sacher, Marc; Heinzmann, Ulrich; Hoeke, Veronika; Krickemeyer, Erich; Glaser, Thorsten; Bouvron, Samuel; Fonin, Mikhail; et al. (Journal of Physics: Condensed Matter)
Keywords: Condensed Matter Physics; General Materials Science

Glutamic acid adsorbed on Ag(110): direct and indirect molecular interactions - Blankenburg, S; Schmidt, Wolf Gero (Journal of Physics: Condensed Matter)

QUANTUM ESPRESSO: a modular and open-source software project for quantum simulations of materials - Giannozzi, Paolo; Baroni, Stefano; Bonini, Nicola; Calandra, Matteo; Car, Roberto; Cavazzoni, Carlo; Ceresoli, Davide; Chiarotti, Guido L; Cococcioni, Matteo; Dabo, Ismaila; Dal Corso, Andrea; de Gironcoli, Stefano; et al. (Journal of Physics: Condensed Matter)

Coherent optoelectronics with single quantum dots - Zrenner, Artur; Ester, P; Michaelis de Vasconcellos, S; Hübner, M C; Lackmann, L; Stufler, S; Bichler, M (Journal of Physics: Condensed Matter)
The optical properties of semiconductor quantum dots are in many respects similar to those of atoms. Since quantum dots can be defined by state-of-the-art semiconductor technologies, they exhibit long-term stability and allow for well-controlled and efficient interactions with both optical and electrical fields. Resonant ps excitation of single quantum dot photodiodes leads to new classes of coherent optoelectronic functions and devices, which exhibit precise state preparation, phase-sensitive optical manipulations and the control of quantum states by electrical fields.

Theoretical and experimental investigations of Coulomb blockade in coupled quantum dot systems - Kaiser, F J; Kohler, S; Hänggi, P; Malecha, M; Ebbecke, J; Wixforth, A; Schumacher, H W; Kästner, B; Reuter, Dirk; Wieck, A D (Journal of Physics: Condensed Matter)

Theoretical study of the localization of excess electrons at the surface of ice - Hermann, A; Schwerdtfeger, P; Schmidt, Wolf Gero (Journal of Physics: Condensed Matter)

Charge and spin dynamics in a two-dimensional electron gas - Pugžlys, A; Rizo, P J; Ivanin, K; Slachter, A; Reuter, Dirk; Wieck, A D; Wal, C H van der; Loosdrecht, P H M van (Journal of Physics: Condensed Matter)

Femtosecond time-resolved five-wave mixing at silicon surfaces - Meier, Torsten; Reichelt, Matthias; Koch, S W; Höfer, U (Journal of Physics: Condensed Matter)
The ultrafast dynamics of photoexcitations at silicon surfaces is investigated using a surface-sensitive purely optical technique. In the experiments, the diffracted second harmonic generated by sequences of ultrashort laser pulses is detected as a function of the time delay between the pulses. It is demonstrated that this five-wave-mixing technique can be used to measure the temporal evolution of the optical polarization and the photoexcited populations at the surface. The experimental results can be reproduced by numerical solutions of optical Bloch equations. The theoretical analysis allows one to investigate which dephasing times and relaxation processes are compatible with experiment. Furthermore, it is outlined how one can describe optical nonlinearities at surfaces using a microscopic theory within the framework of semiconductor Bloch equations.

Femtosecond time-resolved five-wave mixing at silicon surfaces - Meier, Torsten; Reichelt, Matthias; Koch, S W; Höfer, U (Journal of Physics: Condensed Matter)
The ultrafast dynamics of photoexcitations at silicon surfaces is investigated using a surface-sensitive purely optical technique. In the experiments, the diffracted second harmonic generated by sequences of ultrashort laser pulses is detected as a function of the time delay between the pulses. It is demonstrated that this five-wave-mixing technique can be used to measure the temporal evolution of the optical polarization and the photoexcited populations at the surface. The experimental results can be reproduced by numerical solutions of optical Bloch equations. The theoretical analysis allows one to investigate which dephasing times and relaxation processes are compatible with experiment. Furthermore, it is outlined how one can describe optical nonlinearities at surfaces using a microscopic theory within the framework of semiconductor Bloch equations.

Oxidation- and organic-molecule-induced changes of the Si surface optical anisotropy:ab initiopredictions - Schmidt, Wolf Gero; Fuchs, F; Hermann, A; Seino, K; Bechstedt, F; Paßmann, R; Wahl, M; Gensch, M; Hinrichs, K; Esser, N; Wang, S; Lu, W; et al. (Journal of Physics: Condensed Matter)